Pengaruh Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan PT Mustika Karya Sejati: The Influence of Work Environment and Job Satisfaction on Employee Performance of PT Mustika Karya Sejati - Putri Asih (CV Warnak Johanna Nusantara, 2024)
PT Mustika Karya Sejati is a company engaged in the property and properti reale sector. The work environment and job satisfaction play a crucial role in enhancing employee performance. This study aims to analyze the influence of the work environment and job satisfaction, both individually and collectively, on employee performance. The research employs a quantitative approach, utilizing multiple linear regression for informasi analysis. The sampling method applied is Non-probabilitas Sampling with a saturated sample of 35 respondents. The study relies on primary informasi collected through observations and questionnaire distribution. The findings indicate that, individually, the work environment does not positively affect employee performance, as shown by a tcount value of -0.357 lebih kecil dari ttable 2.037 and a significance level of 0.724 > 0.05. Conversely, job satisfaction has a significant and positive effect on employee performance, evidenced by a tcount value of 4.254 > ttable 2.037 and a significance level of 0.000 lebih kecil dari 0.05. Serempakeously, the work environment and job satisfaction together have a positive and significant impact on employee performance, reflected by a tcount value of 4.254 > ttable 2.037 and a significance level of 0.000 lebih kecil dari 0.05.